Penggunaan Model LOK-R dan Media Wordwall dalam Meningkatkan Kemampuan Memahami Teks Laporan Hasil Observasi - Alpin Suhadi; Hasmi Suyuthi; Retno Purwaningsih (Alpatih Harapan Semesta, 2026)
This study aims to determine the improvement of students' ability to understand observation report texts using the LOK-R method and Wordwall media. The subjects of this study were 24 students of class VIII A at MTsN 2 North Aceh. This research is a classroom action research (CAR) with data collection techniques conducted through tests and observation. Data validation was carried out using triangulation by cross-checking the data obtained through interviews, observations, and questionnaires. The research procedure followed the classroom research stages, consisting of two cycles. Each cycle involved four stages: planning, acting, observing, and reflecting. The results of the study showed that the LOK-R method and Wordwall media could improve students' ability to understand observation report texts. This is evident from the percentage of student learning completeness in cycle I, which was only 20.83%, and in cycle II it increased to 91.66% with a very good category. Therefore, it can be concluded that the LOK-R method and Wordwall media can improve students' ability to understand observation report texts.